(untitled) (Sport and Exercise Psychology, 2025)
Curling, often referred to as “chess on ice,” is a sport that blends technical skill, refined strategy, and a strong psychological component. This article explores the intersection between curling and sport psychology, highlighting the impact of factors such as concentration, stress management, team cohesion, and empathy on performance. A review of recent studies reveals that cognitive and psycho-emotional abilities are as decisive as physical and technical preparation. From attentional focus to emotional regulation under high-pressure conditions, psychological processes emerge as central to competitive success. The article provides a reflection that combines academic insights with a more accessible perspective, offering both specialists and general readers an overview of how the mind, alongside the body, shapes excellence in contemporary curling.